Implementasi Fungsi dan Manajemen Kehumasan Direktorat Pengelolaan Media Publik Kementerian Komunikasi dan Informatika dalam Sosialisasi UU KIP - Intan Tanjung Sari; Iwan Awaluddin Yusuf (Program Studi Ilmu Komunikasi, 2012)
The purpose of this study is to determine the implementation of functions and management of public relations (PR) performed by Directorate of Media, Ministry of Communications and Information Technology in the socialization of the acts about Public Information. This study also determines the method and the factors that support as well as hinder the socialization. Based on this study, Directorate of Media has conducted functions and management of PR to socialize the Freedom of Information Law. PR functions used in this study is publicity through the media, writing activity with a theme related news format Freedom of Information Law, website development and web interface, media relations to expand the reach of socialization, and PR function as communication technician. PR Management related to socialization through stages fact finding, planning the socialization mechanisms, action and communication or the realization the plan, and evaluation.